Behind the halal logo - Tukiran, Nur Azira; Ahmad Fadzillah, Nurrulhidayah (Revon Media Sdn Bhd, 2025)
Walk into any supermarket, and you will see the halal logo proudly displayed on packaged foods, beverages, cosmetics, and even pharmaceuticals. For millions of Muslim consumers, this logo is more than a mark; it is a promise. It represents that what they consume or use is permissible, clean, and safe, in line with the principles of halalan toyyiban. But what happens before a product earns the right to display that logo? Behind the scenes, a system of checks, inspections, and evaluations ensures the halal logo is more than just a sticker. At the heart of this system lies the halal audit, a structured process that protects consumers and builds trust in the halal industry.